Personalized embryo transfer guided by rsERT improves pregnancy outcomes in patients with repeated implantation failure - Li, Ning; Zhang, Yisheng; Li, Rufei; Chen, Yulin; Huang, Lin; Tan, Zhuojie; Ban, Xiaoying; Zhou, Ling; Xu, Changlong; Qiu, Ying; Li, Rong (Frontiers in Medicine, 2024)
Introduction: Embryo implantation requires synchronous communication between the embryo and maternal endometrium. Inadequate maternal endometrial receptivity is one of the principal causes of embryo implantation failure (especially repeated implantation failure (RIF)), when biopsied good-quality euploid embryos are transferred. An RNA-Seq-based endometrial receptivity test (rsERT) was previously established to precisely guide successful embryo implantation. Here, we aimed to evaluate the effect of personalized embryo transfer (pET) via rsERT on the clinical outcomes in patients with RIF. Methods: 155 patients with RIF were included in the present retrospective study and were divided into two groups: 60 patients with rsERT and pET (Group rsERT), and 95 patients underwent standard frozen embryo transfer (FET) without rsERT (Group FET). Reproductive outcomes were compared for patients underwent rsERT guided pET and standard FET.Results: 40% (24/60) of the patients underwent rsERT were receptive, and the remaining 60% (36/60) were non-receptive. The positive human chorionic gonadotropin (β-hCG) rate (56.3% vs. 30.5%, P=0.003) and clinical pregnancy rate (43.8% vs. 24.2%, P=0.017) were significantly higher in Group rsERT patients than those in FET group patients. Additionally, Group rsERT patients also showed higher implantation rate (32.1% vs. 22.1%, P=0.104) and live birth rate (35.4% vs. 21.1%, P=0.064) compared with FET patients, although without significance. For subpopulation analysis, the positive β-hCG rate, clinical pregnancy rate, implantation rate and live birth rate from receptive patients were not statistically significant different from those of non-receptive patients.The rsERT can significantly improve the pregnancy outcomes of patients with RIF, indicating the clinical potential of rsERT-guided pET.